Correction: Wang et al. Future Prospects of the Assembly Model for MEP Systems in Chinese Buildings: A Whole Life Cycle Perspective. Appl. Sci. 2024, 14, 6818 - Chun Wang; Peng Ouyang; Xiaodong Liu; Zhihua Zou; Yuanping Wang; Ruiling Wang (Applied Sciences)
In the published paper [...]